A comparative study of the treatment processes applied to "ginsaniban" by healers of Tacloban City - Estoya, Ella Vircelle C.; Lopez, Randy L. (2003)
This study was conducted to determine how healers (priests and "tambalans") of Tacloban City perceive and treat a "possessed" person or the local "ginsaniban". Seven healers were purposively selected (3 priests and 4 "tambalans") who provided information for the research. Data was gathered through the interview method, which entailed the employment of some methods in the "Iskala ng Mananaliksik". After the data was analyzed, the researchers found out that the healer-respondents have similarities and differences in how they view and in how they treat afflicted persons, basically because of variations in their belief systems and frames of reference.